IMPLEMENTATION OF LA DARAR WA LA DIRAR RULES IN THE SYIRKAH MUDHARABAH CONTRACT : CASE STUDY OF KAMPOENG KULINER MAKASSAR - M. Fadel, M. Fadel; Lutfi, Mukhtar; Misbahuddin, Misbahuddin (PT. Altin Riset Publishing, 2025)
The purpose of this research is to analyze the application of the La Darar Wa La Dirar principle in the syirkah mudharabah contract at Kampoeng Culinary Makassar. This research uses a qualitative approach with normative / shar'i, phenomenological, and sociological methods. Informants include managers, employees, and investors of Kampoeng Culinary Makassar, as well as customers, business experts, and muamalah. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis included data reduction, data presentation, and conclusion drawing. The results showed that: (1) The contract implementation mechanism at Kampoeng Culinary Makassar is good, although there are still obstacles that need to be improved to prevent darar between the manager and Sohibul Māl. The process includes four stages: written agreement, fund collection, profit sharing, and contract dissolution. (2) Management efforts in applying the principle of Lā Darār Wa Lā Dirār include the presentation of business proposals, profit and loss projections, cooperation MoUs, the use of cloud-based cashier technology, monthly financial reports, and evaluation meetings with investors. (3) The obstacles faced include the large number of investors, miscommunication in understanding the contract and profit sharing, investors' lack of understanding of financial statements, and unpreparedness to accept the risk of loss. The solutions implemented are consultation, socialization, education, and provision of information to related parties.